Differential sandwich theorem for certain class of analytic functions associated with an integral operator - COTÎRLĂ, Luminița-Ioana; CĂTAȘ, Adriana (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
In this paper we obtain some applications of first order differential subordination and superordination result involving an integral operator for certain normalized analytic function. Mathematics Subject Classification (2010): 30C45.